Uji Keragaman Bobot Pulveres untuk Penyakit Infeksi Saluran Pernapasan Akut (ISPA) pada Apotek di Wilayah Kerja Unit Pelayanan Teknis Puskesmas Bengkalis - Benni Iskandar (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2020)
The demand for pulveres (divide powder) preparations is still being done widely by doctors both doctors in hospitals, clinics or health centers for patients, especially pediatric patients who have difficulty consuming tablets or capsules so that it can be recompiled from solid dosage forms to pulveres dosage form. The purpose of divided powder distribution is to provide convenience and comfort to patients, especially pediatric patients who have difficulty receiving drugs in solid dosage forms. According to data obtained by researchers from all prescriptions collected at UPT Bengkalis health center, that there are still many URI pulveres prescriptions written by doctors in the children's polyclinic room as many as 598 prescriptions in the last six months from September 2018 to February 2019. Based also on data from UPT Bengkalis health center there are thirteen pharmacies in the working area of ​​UPT Bengkalis health center. The results obtained from thirteen pharmacies there are three pharmacies that do not meet the weight uniformity requirements and there are ten pharmacies that meet the weight uniformity requirements set by Pharmacopoeia Indonesia V Edition.